Opportunistic natural experiments using digital telemetry: a transit disruption case study. Issue 9 (1st September 2016) - Stanley, Kevin; Bell, Scott; Kreuger, L. Kurt; Bhowmik, Priyasree; Shojaati, Narjes; Elliott, Alexa; Osgood, Nathaniel D.
ABSTRACT: In the past decade society has entered a technological period characterized by handheld computing that supports input and processing from numerous sensors. Today's mobile phones offer the ability to integrate input from sensors monitoring various external and internal sources (e.g., accelerometer, magnetometer, microphone, GPS, wireless Internet, and Bluetooth). Furthermore, these raw inputs can be integrated and processed in ways that can offer novel representations of human behaviour. As a result, new opportunities to examine and better understand human spatial behaviour are available; one such application is the constant monitoring of a group of people over an extended period of time. Such a research setting lends itself to natural experiments that emerge as a result of regular and on-going observations. We report here on the observation of a natural experiment that took place in the context of a month-long monitoring study of 28 participants using mobile phone-based ubiquitous sensor monitoring. The implications for public health and transportation planning are discussed.